Knowledge and recommendation of oral rehydration solution and zinc for management of childhood diarrhoea among patent and proprietary medicine vendors in Port Harcourt, Nigeria - Emmanuel Firima; Birger Forsberg (Inishmore Laser Scientific Publishing Ltd, 2020)
## Background In Nigeria, where patent and proprietary medicine vendors (PPMVs) provide care in 55% of common paediatric illnesses, child deaths from diarrhoeal diseases stands at 104000; 14% of total all-cause child mortality. Our aim was to investigate PPMVs knowledge of presentation, cause, treatment and prevention of childhood diarrhoea, and their recommendation of oral rehydration solution (ORS) and zinc in the treatment of sick children in Port Harcourt, Nigeria. ## Methods A cross-sectional design, structured questionnaires were administered to 200 PPMVs over six weeks with a 94% response rate. The main outcome variables were knowledge of childhood diarrhoea, and recommendation of ORS and zinc. Knowledge scores were analysed numerically and categorized as satisfactory (score ≥15) and unsatisfactory (score < 15). Multivariate Poisson loglinear regression was used to analyse score ratios. Binomial logistic regression was used to assess the determinants of recommendation of ORS as well as recommendation of zinc. ## Results Overall knowledge of childhood diarrhoea was satisfactory among 47% of PPMVs. Eighty six percent of them reported consistent recommendation of ORS, while 63% of PPMVs consistently recommended zinc. Secondary education (Score Ratio (SR) =1.26, 95% Confidence Interval (CI) =1.01-1.56, P=0.039) and post-secondary education (SR=1.37, 95% CI=1.09 -1.72, P=0.008) were associated with significantly higher knowledge scores. Recommendation of ORS was significantly associated with knowledge score (Adjusted Odds Ratio (AOR) =1.41, 95% CI=1.19-1.66, P<0.001), availability of ORS (AOR=7.26, 95% CI=1.73-30.54, P=0.007) and prescribing of zinc (AOR=5.82, 95% CI=2.03-16.66, P=0.001). Recommendation of zinc was significantly associated with awareness of ORS/zinc guidelines (AOR=5.60, 95% CI=1.07-29.26, P=0.041. ## Conclusions With the low knowledge of presentation, cause, treatment and prevention of childhood diarrhoea among PPMVs, management of childhood diarrhoea by them in the community is unlikely to be optimal. The reported recommendation of ORS and zinc will need to be further investigated and confirmed by direct observation. Educational requirement for PPMVs to operate a drug shop should be increased to at least secondary education level, and supply of ORS/zinc made reliable as these have shown to be important factors in the recommendation of the products.